Achievement of Carbon Emission Disclosure as a Mediator between Factors Increasing Firm Value: Eco-efficiency and Green Innovation - Sari, Petty Aprilia; Rays, Muh.; Purwanti, Purwanti; Hidayat, Imam (International Journal of Energy Economics and Policy, 2024)
Investors today are more interested in investing in that care about the environment, but there are still many companies that focus only on financial gains and ignore environmental issues. Companies are being charged with disclosure of their emissions and climate transaction plans. Companies that disclose Carbon Emission Disclosure have different values in the eyes of investors and other stakeholders. The study aims to determine the impact of Eco-efficiency and Green Innovation on Firm Value by disclosing Carbon Emission as Intervening Variable on Manufacturing Companies listed on the Indonesian Stock Exchange in the period 2019-2023. Research uses a quantitative approach. The samples used in this study were 24 companies selected using purposive sampling techniques. The data used is 120 observations. Hypothesis testing using Ordinary Least Square regression and robust regression with Stata 17.0. The results of the research showed that the eco-efficiency variable had a significant positive impact on Firm Value, Green Innovation had an significant positive effect on Firm Value, Carbon Emission Disclosure had a major positive impact upon Firm Value, Eco-Efficiency had a substantial positive influence on Carbon Emission Disclosure, Green Innovating had a significant positive effect upon Carbon Emission Disclosure, Carbon emission disclosures were unable to mediate the impact of Eco- Efficiency on Firm Value, and Carbon Emission Disclosure was capable of mediating the green innovation's impact on the Firm Value.